Autonomous vibration control of beams utilizing intelligent excitation adaptability - Chen, Shuai; Wang, Yilong; Wu, Qianjing; Zhang, Xiaoyun; Cao, Dengqing; Wang, Biao (International journal of mechanical sciences, 2025)
•An intelligent excitation adaptability method for vibration control (IEA-VC) of beams is proposed.•The IEA-VC autonomously switches between low and high dynamic stiffness modes.•A fast excitation frequency recognition algorithm operates solely based on displacement signals.•The knowledge-based algorithm precisely identifies excitation frequencies within milliseconds.•The IEA-VC achieves both resonance elimination and high-performance vibration isolation. Undesirable mechanical vibrations in beam structures deteriorate the structural integrity, operational reliability, and service lifespan of systems across various engineering and industrial applications. However, most existing vibration methods for beam structures struggle in dynamic and complex environments due to their continuum nature and nonlinear behavior. To achieve autonomous vibration control across the full spectrum, this article proposes an intelligent excitation adaptability (IEA) concept for real-time vibration control of beam structures under frequency-varying excitations. The IEA system is composed of a stiffness-variable electromagnetic appliance, a real-time excitation frequency recognition algorithm, and an autonomous stiffness-switching program. The electromagnetic appliance, arranged in a nesting-type configuration, consists of six-ring permanent magnets (PMs) and six coil windings (CWs). By tuning the magnitude and direction of the current in CWs, a high (HDS) or low (LSD) dynamic stiffness state can be assigned to the IEA system. We develop a recognition algorithm to rapidly and accurately identify the excitation frequency solely based on displacement response signals derived from a nonlinear dynamic model of the beam. Simultaneously, the autonomous stiffness regulation automatically selects either HDS or LSD mode for optimal vibration suppression. The theoretical and experimental results demonstrate that the frequency recognition and stiffness switching processes of the IEA vibration control (IEA-VC) system are fast (min. to 17 ms), accurate, and reliable. Furthermore, the IEA-VC system significantly mitigates resonance (e.g., from 11.48 dB to -1.35 dB) and achieves full-spectrum vibration suppression compared to traditional vibration control approaches. [Display omitted]